Integrated multitrophic aquaculture supply chain fish traceability with blockchain technology, valorisation of fish waste and plastic pollution reduction by seaweed bioplastic: A study in tuna fish aquaculture industry - John, Ezhilarasan Peter; Mishra, Umakanta (Journal of cleaner production, 2024)
The high demand for tuna, coupled with unsustainable supply chain practices, has triggered illegal fishing, overfishing, and environmental damage, including bycatch, pollution, and climate change impacts. To address these issues, the world urgently needs sustainable alternatives to meet tuna demand while preserving our oceans, marine species, and the environment. In this paper, a sustainable three-layer tuna fish supply chain model consisting of a single farmer, processor, and retailer is developed for two different quality levels of tuna fish. Green technology and integrated multi-trophic aquaculture (IMTA) methods are implemented at the farmer stage to reduce emissions and ocean pollution. Fish waste utilization technology, seaweed bioplastic packaging technology, and green technologies are implemented at the processor stage to reduce fish waste, plastic pollution, and carbon emissions. Blockchain technology is implemented for the traceability and transparency of the whole supply chain in order to avoid illegal and unsustainable tuna fish entering the market. The optimal solutions of the average integrated total profit are found by using the particle swarm optimization (PSO) algorithm in Python platform. The farmer's and processor's emission costs are reduced by 80% by investing in green technology. The transportation cost is also reduced. The fish waste utilization and plastic waste minimization costs of processors are reduced by more than 95% by investing in fish waste utilization and seaweed bioplastic packaging technology. The concavity of the average integrated total profit function is shown in a 3D graph. The optimal solution, sensitivity analysis, numerical examples, and managerial implications are presented for the tuna fish supply industries. The proposed model is applicable to any food processing industry. [Display omitted] •A sustainable three-layer optimization model is developed for the tuna fish supply chain.•CO2 emissions are reduced in the supply chain using green technology.•Fish waste utilization technology is implemented to reduce fish waste.•Seaweed bioplastic technology is introduced to reduce single-use plastic pollution.